2016
DOI: 10.5454/mi.10.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Culturable Bacterial in Various Parts of Luwak’s (Paradoxurus hermaprodithus javanica) Gastrointestinal Tract

Abstract: Coffee is an important commodity and one of the most popular beverages in the world. Over 2.25 billion cups of coffee are consumed in the world every day (Ponte 2002). In 2012, Indonesia ranked third after Brazil and Vietnam in the global production of green coffee beans (USDA 2012). Five species of coffee that are commonly cultivated in the world include Coffea arabica, C. canephora, C. robusta, C. liberica, and C. excelsa (Doyle et al., 2001). In Indonesia C. robusta and C. arabica are the species mostly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…A previous study reported that G. frateurii , G. japonicus are closest to each other ( Malimas et al, 2009 ). Our study suggests that the civet cat fecal microbiome is dominated by Gluconobacter , which was detected in a previous study using general cultivation methods ( Suhandono et al, 2016 ). In fact, a previous study of the cacao microbiome reported that Gluconobacter species is hardly detected by the cultivation method; however, using metagenomics and shotgun sequencing, the presence of Gluconobacter species was observed ( Agyirifo et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A previous study reported that G. frateurii , G. japonicus are closest to each other ( Malimas et al, 2009 ). Our study suggests that the civet cat fecal microbiome is dominated by Gluconobacter , which was detected in a previous study using general cultivation methods ( Suhandono et al, 2016 ). In fact, a previous study of the cacao microbiome reported that Gluconobacter species is hardly detected by the cultivation method; however, using metagenomics and shotgun sequencing, the presence of Gluconobacter species was observed ( Agyirifo et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…The unique gut microbiome of the civet cat might contribute to the characteristic physical properties and metabolite content of kopi luwak beans. A recent isolation and cultivation approach identified the bacterial species in the civet cat gastrointestinal tract, including Bacillus , Pseudomonas , Pantoea , Escherichia , Lactobacillus , Ochrobactrum and Kocuria ( Suhandono et al, 2016 ). However, the study was unable to define the entire microbiome because some of the gut bacteria were unculturable ( De Jager & Siezen, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The total LAB number was between 0.14 x 10 7 -3.71 x 10 8 cfu/ml. This result lower than those reported by Suhandono et al [15] and Muzaifa et al [16]. Table 1 indicated that the total number of LAB increased from the stomach to the small intestine and colon.…”
Section: A Quantification and Isolation Of Labcontrasting
confidence: 61%
“…Manuscript to be reviewed methods (Suhandono et al, 2016). In fact, a previous study of the cacao microbiome reported that Gluconobacter species is hardly detected by the cultivation method; however, using metagenomics and shotgun sequencing, the presence of Gluconobacter species was observed (Agyirifo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed including Bacillus, Pseudomonas, Pantoea, Escherichia, Lactobacillus, Ochrobactrum, and Kocuria (Suhandono et al, 2016). However, the study was unable to define the entire microbiome because some of the gut bacteria were unculturable (de Jager & Siezen, 2011).…”
Section: Introductionmentioning
confidence: 99%